Accumulation of iron in the soil-plant system in a metal industry area = Kumulacja żelaza w układzie gleba-roślina na terenie przemysłu metalowego - Fruzińska, Róża (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of research on the content of iron in a subtotal form in the soils of metal industry areas and the content of iron in the grass growing in the test area. Research on the content of iron in soils and grasses was carried out in 2009-2010.
Keywords: przemysł metalowy; zanieczyszczenie gleby; kumulacja żelaza; metal industry; soil contamination; bioaccumulation of iron